STUDI PENATAAN KEMBALI TEMPAT PEMAKAMAN UMUM(Studi Kasus TPU Kembangarum Kota Semarang) - Diharto, Autor (TATAL, 2011)
Semarang City has 11 public cemeteries covering 45.88 hectares. Of these eleven commonburial place, a place that is relatively difficult to set a public cemetery located in the Village KembangarumKalipancur Ngaliyan District of Semarang, because (1) the condition is contoured to the slope up to 45%,(2) irregular shape, and (3) placement of the graves have not been arranged properly. So it is necessary tostudy the effectiveness of land use in the realignment of the tomb with a case study in a public cemeteryKembangarum. The analysis used the general arrangement of the cemetery Kembangarum are (1) landmanagement notice or follow the existing contour lines, (2) use of land as closely as possible to thecemetery by taking into account infrastructure and greening the existing system with cut and fill, (3) slopeof the road concerned convenience and safety of users made <10%. Making the zone to facilitate thearrangement of the tomb and the tomb of the separation of both Muslims and non Muslims. Making theexisting contours of the zone considered, so there is a large zone (can accommodate many tombstones) anda small zone (holds little headstone). The results of the general arrangement of the cemetery there were 42zones Kembangarum tomb consisting of three zones of the tomb has been partially filled and 39 zones arestill empty tomb. The number of total existing headstone headstone 2316; already filled 184; and 2132headstone unfilled. To change the image of the cemetery as a tourist pilgrimage Kembangarum gazeboplaced some specific location, a garden, and the lamps lit at night.Keyword : Effectiveness, Land Use, Places of Public Cemetery